Computational Revision of the Mechanism of the Thorpe Reaction - Victor A. Lucas-Rosales; Marco A. García-Revilla; J. Oscar C. Jiménez-Halla (Chemistry Proceedings, 2022)
The Thorpe reaction is described as a self-condensation of nitriles in the presence of a basic catalyst producing β-enaminonitriles. We performed theoretical calculations within the Density Functional Theory (DFT) framework at the ωB97XD/def2-svpd level to explore different mechanistic proposals when propionitrile is used as a reagent and sodium ethoxide (EtONa) as a catalyst. Furthermore, the influence of different solvents, such as ethanol (EtOH), tetrahydrofuran (THF), 1,2-dimethoxyethane (DME), and propionitrile (EtCN), was assessed. Finally, we also evaluated the effect of the fluorine group (-F), compared to the methyl group (-CH3), substituted in the α position of acetonitrile (MeCN). Our theoretical findings agree with different experimental reports on the Thorpe reaction.